A NEW ROBUST ANALYTICAL METHOD DEVELOPMENT, VALIDATION, AND STRESS DEGRADATION STUDIES FOR ESTIMATING RITONAVIR BY UV-SPECTROSCOPY AND HPLC METHODS - PARVEEN, NEHA; ROUTH, TIASHA; GOSWAMI, AMIT KUMAR; MONDAL, SUMANTA (International Journal of Applied Pharmaceutics, 2023)
Objective: To specify ritonavir and its commercial dosage form, the current study set out to design and validate concise, precise, and efficient high-performance liquid chromatography and spectrophotometric methods. The developed spectroscopy and chromatographic methods are reliable, precise, accurate, and specific for estimating ritonavir. Methods: The method is superior to previously described methods due to its shorter retention duration, use of an affordable and easily accessible mobile phase, UV detection, and improved peak resolution. The maximum absorbance was determined by analysing multiple concentration ranges of ritonavir at 10-60 µg/ml using the UV-spectrophotometric method. The chromatographic separation was performed with a mobile phase composed of acetonitrile and 0.1% formic acid (1:1 v/v) pumped at a 1.0 ml/min flow rate on a phenyl (150 x 4.6 mm, 3.5 µm) column. Results: Obeyed Beer-Lambert law over the 10-60 µg/ml and 25-150 µg/ml concentration range of ritonavir for the UV-spectrophotometric and HPLC methods, respectively. The absorbance at 273 nm was selected as the maximum absorbance throughout the UV-spectroscopic study. The detection and quantification limits for UV-spectroscopic are 0.89 and 2.93 µg/ml, whereas for the HPLC method are 0.78 and 2.57 µg/ml, respectively. In the accuracy and precision validation studies, the amount of recovery and percentage of RSD was excellent with acceptance limits as per International Conference on Harmonization (ICH) guidelines. Conclusion: The suggested method has been approved following standards established by the ICH. The developed methods can be employed to analyse ritonavir API and pharmaceutical dosage forms and provide better specificity, excellent separation, and specified analyte and degradation substances.